Questionnaires of self-perception poorly correlate with instability elicited by walking balance perturbations. - Andrew D Shelton; Jessica L Allen; Vicki S Mercer; Jeremy R Crenshaw; Jason R Franz (PLoS ONE, 2024)
Rehabilitation to prevent falls should not only directly address intrinsic and extrinsic factors, but also the neuropsychology of falls to promote safe and independent mobility in our aging population. The purpose of this study was to determine the relation between falls self-efficacy and objective responses to a series of walking balance perturbations. 29 healthy younger adults and 28 older adults completed four experimental trials, including unperturbed walking and walking while responding to three perturbations: mediolateral optical flow, treadmill-induced slips, and lateral waist-pulls; and three self-reported questionnaires: Activity-specific Balance Confidence, Falls Efficacy Scale, and the Fear of Falling Questionnaire-Revised. We quantified stabilizing responses as a change in margin of stability from unperturbed walking. Older adults generally exhibited larger instability than younger adults in response to walking balance perturbations. Only the Fear of Falls Questionnaire-Revised showed an increase in perceived falls risk for older adults. We found no significant correlations for older adults between any balance perturbation response and questionnaires of self-perception. Given the disconnect between self-perceived falls risk and responses to walking balance perturbations, rehabilitation to prevent falls while maintaining mobility and independence will likely require personalized techniques that combine neuromuscular training with approaches for neurophysiological reeducation.